Directing Trophic Divergence in Plant-Pathogen Interactions: Antagonistic Phytohormones With NO Doubt? - Huang, Shuanglong; Zhang, Xuehua; Fernando, W. G. Dilantha (Frontiers in Plant Science, 2020)
A fundamental process culminating in the mechanisms of plant-pathogen interactions is the regulation of trophic divergence into biotrophic, hemibiotrophic and necrotrophic interactions. Plant hormones, of almost all types, play significant roles in this regulatory apparatus. In plant-pathogen interactions, two classical mechanisms underlying hormone-dependent trophic divergence are long recognized. While salicylic acid dominates in the execution of host defense response against biotrophic and early-stage hemibiotrophic pathogens, jasmonic acid and ethylene are key players facilitating host defense response against necrotrophic and later-stage hemibiotrophic pathogens. Evidence increasingly suggests that trophic divergence appears to be modulated by more complex signaling networks. Acting antagonistically or agonistically, other hormones such as auxins, cytokinins, abscisic acid, gibberellins, brassinosteroids and strigolactones as well as nitric oxide are emerging candidates in the regulation of trophic divergence. In this review, the latest advances in the dynamic regulation of trophic divergence are summarized, emphasising common and contrasting hormonal and nitric oxide signaling strategies deployed in plant-pathogen interactions.